Analyzing Ecotheology from The Perspective of Islam and Christianity: An Examination of Soren Kierkegaard’s Existentialism Philosophy - Aditama Aditama; Nafik Muthohirin; Muhammad Rafliyanto (Universitas Muhammadiyah Malang, 2023)
Religious teachings are closely related to the ecological dimension which, after being reinterpreted, eventually led to the term ecotheology. Through previous studies, it was found that one of the religions that contain these values ​​is Islam and Christianity. This study aims to answer the formulation of the problem in the form of how the concept of ecotheology exists in Islam and Christianity and how to compare the concept of ecotheology in the two religions in the study of Soren Kierkegaard's existentialist philosophy. This research is a literature study with a comparative approach. The findings of this study conclude that in both religions there is a strong emphasis on the role of humans as guardians of the environment, the concept of environmental justice, the position of God as giver of responsibility, the existence of collectivity, and spiritual values. in the ecological role of humans. In Islam itself, through the Nahdlatul Ulama and Muhammadiyah organizations, the collectivity is very visible. The main difference between the two lies in the doctrinal footing and organization of the movement.